DAMPAK PARIWISATA TERHADAP PEMANFAATAN RUANG PERMUKIMAN DI KAWASAN PESISIR CRISTO REI DESA METIAUT, KOTA DILI - TIMOR LESTE - Jeovanio Dos Santos Ribeiro; I Komang Gede Santhyasa; Ni. G. A. Diah Ambarwati Kardinal (UNHI PRESS, 2022)
Developments in Cristu rei have been very rapid in the 11 years since the arrangement. Lastly, the increasing use of built-up space in coastal areas caused by the development of the Cristo rei tourism sector of tribe will affect the carrying capacity or environmental capacity problem formulation how to use space in coastal areas Cristo rei ethnic group Metiaut moment and how tourism impacts on spatial patterns settlement coastal area Cristo rei tribe Metiaut Destination from this research for identify use of space in the coastal area of ??Cristo rei tribe of Dili, Timor Leste and to know how is the impact of tourism on the spatial pattern of settlements in the coastal area of ??Cristo rei tribe benefits from this research providing input to the district government (Kabupaten ) Dili for policies related to the development of the coastal area Cristo rei tribe of Dili Timor Leste and provide understanding to the community on the importance of their role in supporting government programs, thus bringing positive impact on the economy of the Cristo rei community tribe , Dili Timor Leste, the approach used is a qualitative and quantitative approach with a collection technique data using visual plotting observations in the Cristo rei coastal tribes Metiaut and interview via zoom (zoom application) literature study documentation of data analysis techniques with descriptive methods and plotting maps. impacts that affect land change from the physical aspect, namely the change in land use from undeveloped to built is improving the community's economy from the impact of tourism activities in tribe Metiaut Cristo rei, while the change in land use to trade and services is affected by the location of the land close to tourist attractions, accessibility to Cristo rei, and the existence of tourism activities in the Cristo rei coastal area of tribe Metiautthe results of this study 1. at present the impact of the use of built space in the coastal area of ??Cristo rei Suku Metiaut has not had a big impact on the environment. 2.land use change from vacant land into settlements due to the increasing number of people working in the tourism sector residing in the Metiaut tribe and population growth, changes land use from vacant land into tourism facilities is caused by increased tourism activities that are growing in the 11 years since the arrangement Lastly, the use of space from residential houses into trade and service facilities caused by a tourist attraction, transforming the residence into a guest house hotel bars and cafes as a necessity to support tourism activities in Cristo rei tribe Metiaut.